Corporate Social Responsibility and Competitive Strategies: The Moderating Role of Governance Performance and Firm's Performance - Ghareibeh Esmailikia; Mahdis Naseri (پژوهش‌های تجربی حسابداری)
The purpose of this research is to examine the impact of corporate social responsibility (CSR) and competitive strategies on the moderating roles of governance performance and firm performance, based on value-creation indicators. The research sample comprises 1,660 observations from 166 companies listed on the Tehran Stock Exchange over the period from 2013 to 2022. Data were analyzed using multivariate linear regression. The results indicate that corporate social responsibility has a positive and significant impact on both cost leadership and differentiation strategies. Among the three components of governance performance, audit committee independence and the efficiency of the internal audit unit enhance the effect of CSR on the cost leadership strategy; however, board independence does not play a moderating role in this relationship. Additionally, among the governance performance components, only the efficiency of the internal audit unit strengthens the impact of CSR on the differentiation strategy. Furthermore, economic value added, and market value added reinforce the influence of CSR on both cost leadership and differentiation strategies. Enhancing governance performance through the adoption of corporate governance principles, alongside strategic planning to improve firm performance based on value-creating indicators, strengthens the relationship between CSR and competitive strategies, ultimately benefiting the company. Given the significance of governance performance and the role of CSR in competitive strategies, managers can create value and legitimacy for the firm in society while achieving a competitive advantage.